Natural extracellular nanovesicles and photodynamic molecules: is there a future for drug delivery?. (1st January 2017) - Kusuzaki, Katsuyuki; Matsubara, Takao; Murata, Hiroaki; Logozzi, Mariantonia; Iessi, Elisabetta; Di Raimo, Rossella; Carta, Fabrizio; Supuran, Claudiu T.; Fais, Stefano
Abstract: Photodynamic molecules represent an alternative approach for cancer therapy for their property (i) to be photo-reactive; (ii) to be not-toxic for target cells in absence of light; (iii) to accumulate specifically into tumour tissues; (iv) to be activable by a light beam only at the tumour site and (v) to exert cytotoxic activity against tumour cells. However, to date their clinical use is limited by the side effects elicited by systemic administration. Extracellular vesicles are endogenous nanosized-carriers that have been recently introduced as a natural delivery system for therapeutic molecules. We have recently shown the ability of human exosomes to deliver photodynamic molecules. Therefore, this review focussed on extracellular vesicles as a novel strategy for the delivery of photodynamic molecules at cancer sites. This completely new approach may enhance the delivery and decrease the toxicity of photodynamic molecules, therefore, represent the future for photodynamic therapy for cancer treatment.